2004
DOI: 10.1243/0954407042580002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of loss mechanisms in a pushing metal V-belt continuously variable transmission. Part 3: Belt slip losses

Abstract: The power transmission efficiency of continuously variable transmissions (CVTs) based on the pushing metal belt is acknowledged to be lower than that of discrete ratio alternatives. This tends to negate the potential fuel economy benefits that are obtained by improved engine/load matching with a CVT. This series of three papers details an investigation into the loss mechanisms that occur within the belt drive as a first step to obtaining improvements in efficiency. This third paper follows on from two previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 7 publications
3
30
0
Order By: Relevance
“…Additionally, laser displacement sensors were installed in order to detect the changes in the pitch radii of CVT pulleys and to determine the speed and torque losses under different operating conditions. Akehurst et al [10][11][12] investigated the power transmission efficiency of a metal V-belt CVT drive. The belt was constructed from several hundred segments held together by steel band sets.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, laser displacement sensors were installed in order to detect the changes in the pitch radii of CVT pulleys and to determine the speed and torque losses under different operating conditions. Akehurst et al [10][11][12] investigated the power transmission efficiency of a metal V-belt CVT drive. The belt was constructed from several hundred segments held together by steel band sets.…”
Section: Introductionmentioning
confidence: 99%
“…The torque loss of CVT in power transmission consists of three parts [11][12][13]: (1) torque loss due to band friction; (2) pulley deflection loss; (3) belt slip loss.…”
Section: Cvt Torque Loss and Efficiency Modelsmentioning
confidence: 99%
“…(42), which was based on the average values of CVT torque losses. Previous studies [3][4][5]14] have shown that the efficiency of metal belt CVT can be expressed as a function of ratio and input torque, which is expressed as η = η(i,T in ). The CVT efficiency map that changes with ratio and input torque at η p = 2000 r/min is shown in Figure 5…”
Section: Bench Test Performance and Cvt Efficiency Calculationmentioning
confidence: 99%
“…Numerous studies on the efficiency of CVT and gearbox have been conducted through bench tests in China and abroad. Akehurst et al [3][4][5] used bench tests to study torque losses in a metal belt CVT, which were caused by the relative sliding motion between belt segments and bands. They then forecasted and studied torque losses between belt segments and bands caused by the bending and deformation of the pulley based on experimental observations of pulley deflections.…”
Section: Introductionmentioning
confidence: 99%